Differentiating Acute Rejection From Preeclampsia After Kidney Transplantation. Issue 6 (June 2021) - Yin, Ophelia; Kallapur, Aneesh; Coscia, Lisa; Constantinescu, Serban; Moritz, Michael; Afshar, Yalda
Abstract : OBJECTIVE: To evaluate the clinical and laboratory characteristics in pregnancy that differentiate preeclampsia from acute renal allograft rejection and to investigate the maternal, neonatal, and graft sequelae of these diagnoses. METHODS: We conducted a retrospective case-controlled registry study of data abstracted from Transplant Pregnancy Registry International deliveries between 1968 and 2019. All adult kidney transplant recipients with singleton pregnancies of at least 20 weeks of gestation were included. Acute rejection was biopsy proven and preeclampsia was diagnosed based on contemporary criteria. Variables were compared using χ 2, Fisher exact, and Wilcoxon rank sum tests as appropriate. Multivariable linear regression was used to analyze preterm birth. Kaplan-Meier curves with log-rank test and Cox proportional hazards model were used to compare graft loss over time. RESULTS: There were 26 pregnant women with biopsy-confirmed acute rejection who were matched by the year they conceived to 78 pregnant women with preeclampsia. Recipients with acute rejection had elevated peripartum serum creatinine levels (73% vs 14%, P <.001), with median intrapartum creatinine of 3.90 compared with 1.15 mg/dL ( P <.001). Conversely, only patients with preeclampsia had a significant increase in proteinuria from baseline. Although there were no significant differences in maternal outcomes, graft loss within 2 years postpartum (42% vs 10%) and long-term graft loss (73% vs 35%) were significantly increased in recipients who experienced acute rejection ( P <.001 for both). The frequency of delivery before 32 weeks of gestation was 53% with acute rejection and 20% with preeclampsia. After controlling for hypertension and immunosuppressant use, acute rejection was associated with higher frequency of delivery at less than 32 weeks of gestation (adjusted odds ratio 4.04, 95% CI 1.10–15.2). CONCLUSION: In pregnancy, acute rejection is associated with higher creatinine levels, and preeclampsia is associated with increased proteinuria. Acute rejection in pregnancy carries a risk of prematurity and graft loss beyond that of preeclampsia for kidney transplant recipients. FUNDING SOURCE: The Transplant Pregnancy Registry International is supported in part by an educational grant from Veloxis Pharmaceuticals. Abstract : After kidney transplant, acute rejection presents differently from preeclampsia in pregnancy and confers higher risk of graft loss and preterm birth.